NGHIÊN CỨU PHÂN HỦY PENTACLOPHENOL TRONG NƯỚC BẰNG HỆ OXY HOÁ PERCARBONIC ACID - Nguyễn, Thị Năng; Vũ, Ngọc Duy; Nguyễn, Kim Thuỳ; Bùi, Duy Linh; Lê, Bảo Hưng; Nguyễn, Thị Bích Việt (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
PENTACHLOROPHENOL REMOVAL FROM AQUEOUS SOLUTIONS BY PERCARBONIC ACID-BASED OXIDATION SYSTEMSIn this work, the degradation of a persistent organic pollutant, pentachlorophenol (PCP) by a green oxydation system based on peroxymonocarbonate (HCO4-) was studied. Different factors including pH, HCO3- concentration, metal ion catalyst, temperature, and UV irradiation were investigated for their effects on PCP degradation. The results showed that among five tested metal ions (Co2+, Ni2+, Fe2+, Cu2+, Mn2+), Co2+ gave the best catalytic activity. The optimum degradation of PCP was obtained at the concentration of HCO3- and H2O2 of 10 mM and 25 mM, respectively, catalyzed by the presence of 0.1 mg/L Co2+ ion at the intrinsic pH value of the system (8÷10). Moreover, UV irradiation remarkably enhanced the radical formation in the oxydation system, which led to higher degradation efficiencies. The results of COD and TOC removal and LC/MS/LS analysis clearly revealed the potential of complete mineralization of PCP by the oxydation system H2O2/HCO3-/Co2+/UV.